Determining Arabic Language Proficiency: An Examination of Grammar Mastery, Active Usage, and Discipline of Linguistic - Mukmin, Mukmin; Hidayah, Nurul; Haya, Arifah Salma; Md Ali, Nurul Jawahir; Abdullah, Abdurrahman Wahid (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
Arabic language proficiency is a vital outcome of pesantren (Islamic boarding school) education, as these institutions are expected to produce graduates who are not only capable of understanding Arabic texts but also able to communicate effectively in the global context. In line with this expectation, Arabic language instruction within pesantren often places disproportionate emphasis on grammatical rules (nahwu), while overlooking the importance of active usage and linguistic discipline. However, it is precisely these aspects, active engagement and disciplined usage, that serve as the foundation for strong language performance among students. This article examined the key determinants of Arabic language proficiency among students at Pesantren Aishwa Nahla by examining their mastery of grammar (nahwu), level of active engagement, and consistency in linguistic discipline. A correlational research method was employed to collect and analyze data from a randomly selected sample of students at the pesantren. The instruments used included written tests and questionnaires. The findings revealed that most students demonstrate a solid understanding of Arabic grammar and show a relatively high level of active language use. Notably, linguistic discipline emerged as the most influential factor contributing to students’ Arabic language competence. These results underscored the need for an instructional approach that emphasized the habitual and integrated use of Arabic, enabling students to maintain focus and discipline throughout the language acquisition process within the pesantren environment. This research contributes to the development of effective Arabic language teaching strategies in Islamic educational institutions within the pesantren system.